1989
DOI: 10.1007/bf00441907
|View full text |Cite
|
Sign up to set email alerts
|

Displaced distal radius fractures

Abstract: A comparison of the radiographical and functional results after displaced distal radius fractures in 41 patients treated by external fixation (EF), 36 patients treated by functional bracing in supination (FUSU), and 49 patients treated by dorsal plaster immobilization (DPI) was performed. The rate of initial complications after EF was 53%, compared with 22% after FUSU and 14% after DPI. The radiographical result after EF was significantly better than after nonoperative treatment, but the functional result afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Patients were followed monthly till 6 months and then 3 monthly till final followup at 12 months. Functional evaluation was done using Solgaard scoring modified from Gartland and Werley (Table 2) [17,18] . [17,18] .…”
Section: Surgical Techniquementioning
confidence: 99%
“…Patients were followed monthly till 6 months and then 3 monthly till final followup at 12 months. Functional evaluation was done using Solgaard scoring modified from Gartland and Werley (Table 2) [17,18] . [17,18] .…”
Section: Surgical Techniquementioning
confidence: 99%
“…Comminution of the fracture resulted in a 2.5 times increased risk of requiring surgical repair. The biomechanical impact of these fracture patterns are significant as they can lead to weakness, chronic pain, deformity, arthritis, and a tendon excursion mechanical disadvantage, particularly if left untreated [14, 26]. As a result, surgeons will typically pursue fixation for fractures with these characteristics [5, 26, 28].…”
Section: Discussionmentioning
confidence: 99%
“…Over 640,000 distal radius fractures occur annually in the United States [7, 21], representing one-sixth of all fractures treated in emergency departments [7, 15]. While studies have shown a bimodal occurrence affecting younger males and elderly populations [7, 18, 26], distal radius fractures tend to increase dramatically with advancing age [6, 31]. In addition, distal radius fractures have been reported to be 4 times more common in women, particularly after the age of 35 [17, 29], likely owing to the increasing presence of osteopenia in this patient population [25, 29].…”
Section: Introductionmentioning
confidence: 99%
“…At follow-up the functional outcome was assessed by the method described by Solgaard (modified from Gartland and Werley) [3,10,13] (Table 3). The range of motion was measured by a goniometer, and grip strength was measured using a 'My-gripper dynamometer'.…”
Section: Functional Outcomementioning
confidence: 99%
“…Re-manipulation and application of a new cast often results in an unsatisfactory radiological outcome and this may then require surgical treatment with external fixation [6]. In the literature the treatment period with external fixation varies from 4-8 weeks [6,7,12,13]. The purpose of this study was to compare 2 treatment protocols of unstable distal radial fractures using either 3 or 5 weeks of external fixation.…”
Section: Introductionmentioning
confidence: 99%